Zhegalkin Zebra Motives Digital Recordings of Mirror Symmetry - Stienstra, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
Zhegalkin zebra motives are tilings of the plane by black and white polygons representing certain F²-valued functions on ℝ². They exhibit a rich geometric structure and provide easy to draw insightful visualizations of many topics in the physics and mathematics literature. The present paper gives some pieces of a general theory and a few explicit examples. Many more examples will be shown in the forthcoming article "Zhegalkin zebra motives: algebra and geometry in black and white".